Algeria : Stabilization and Transition to Market - Laframboise, Nicole (Occasional Papers; Occasional Paper ;, 1998)
This paper offers Algeria's recent experience with macroeconomic stabilization and systemic transformation from a centrally planned to a market economy. The analyses focuses on the period since 1994 when Algeria embarked on a comprehensive reform program that has benefitted from IMF support, first through a one-year Stand-by Arrangement, and from May 1995, through a three-year arrangement under the Extended Fund Facility. To better understand this experience, this paper provides some background information on Algeria's political history and economic developments during the period preceding the Stand-By arrangement.